Electron Signatures of Reconnection in a Global eVlasiator Simulation. Issue 14 (20th July 2022) - Alho, M.; Battarbee, M.; Pfau‐Kempf, Y.; Khotyaintsev, Yu. V.; Nakamura, R.; Cozzani, G.; Ganse, U.; Turc, L.; Johlander, A.; Horaites, K.; Tarvus, V.; Zhou, H.; et al.
Abstract: Geospace plasma simulations have progressed toward more realistic descriptions of the solar wind–magnetosphere interaction from magnetohydrodynamic to hybrid ion‐kinetic, such as the state‐of‐the‐art Vlasiator model. Despite computational advances, electron scales have been out of reach in a global setting. eVlasiator, a novel Vlasiator submodule, shows for the first time how electromagnetic fields driven by global hybrid‐ion kinetics influence electrons, resulting in kinetic signatures. We analyze simulated electron distributions associated with reconnection sites and compare them with Magnetospheric Multiscale (MMS) spacecraft observations. Comparison with MMS shows that key electron features, such as reconnection inflows, heated outflows, flat‐top distributions, and bidirectional streaming, are in remarkable agreement. Thus, we show that many reconnection‐related features can be reproduced despite strongly truncated electron physics and an ion‐scale spatial resolution. Ion‐scale dynamics and ion‐driven magnetic fields are shown to be significantly responsible for the environment that produces electron dynamics observed by spacecraft in near‐Earth plasmas. Plain Language Summary: The near‐Earth space environment is driven by the solar wind, a thin mixture of ions (mostly protons) and electrons carrying the magnetic field of the Sun. The interaction of this plasma with the Earth's magnetic field produces space weather phenomena, such as aurorae and geomagnetic storms. Supercomputer simulations are an invaluable tool in studying the environment, providing a global view of our magnetosphere—as far as there is enough computational power to resolve the relevant physical processes. Modern simulation codes, such as Vlasiator, can model the environment in great detail at least for the behavior of the ions, providing new insights beyond previous fluid‐scale models. However, detailed electron physics is required to fully understand the near‐Earth space environment at microscales, especially at reconnection sites where the magnetic fields from the Earth and Sun interact. This work uses the new eVlasiator module of Vlasiator to probe electron physics on a global scale, showing electron behavior that is consistent with satellite observations at several locations. Key Points: We present a survey of kinetic electron distribution functions in a global Vlasov model of the Earth's magnetosphere Ion‐scale background fields yield electron distributions consistent with Magnetospheric Multiscale observations Parallel electric fields are observed at the magnetopause, coincident with a flat‐top electron distribution